Potato Psyllid (Hemiptera: Triozidae) Behavior on Three Potato Genotypes With Tolerance to 'Candidatus Liberibacter solanacearum'. Issue 2 (15th April 2020) - Fife, Austin N; Cruzado, Karin; Rashed, Arash; Novy, Richard G; Wenninger, Erik J
Abstract: The potato/tomato psyllid Bactericera cockerelli (Šulc) transmits ' Candidatus Liberibacter solanacearum' (Lso) (also known as ' Candidatus Liberibacter psyllaurous'), the bacterium associated with zebra chip disease (ZC) in potato. When disease incidence is high, ZC causes large economic losses through reductions in potato yield and tuber quality. No commercial potato variety has been found totally resistant to the pathogen. We evaluated host acceptance behaviors using no-choice assays on three breeding clones derived from Solanum chacoense Bitter with putative tolerance to Lso and/or ZC as part of an effort to determine whether the disease tolerance observed in those breeding clones was related to effects on psyllid settling behavior. We also counted the number of eggs laid and nymphs hatched on the different genotypes to observe any differences in reproduction. The potato variety 'Russet Burbank' was used as a susceptible control. Probing frequency and female walking duration were greater on Russet Burbank than the other genotypes. Oviposition did not differ among genotypes. However, female psyllids on two of the Lso-tolerant genotypes displayed reduced fertility 18–24 d after confinement with a male, relative to females on Russet Burbank. These results suggest that although the germplasms display minor abiotic activity on psyllid fertility, tolerance to Lso may be more strongly linked with plant tolerance to the pathogen rather than effects on host acceptance behaviors.